Pengaruh Budaya organisasi dan motivasi kerja terhadap disiplin kerja pegawai Kementerian Hukum dan HAM pada Lembaga Pemasyarakatan Perempuan Kelas II A Jakarta - Dwiarko Nugrohoseno; Aldi Martua Hasibuan (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the effect of organizational culture and work motivation on the work discipline of Ministry Of Low And Human Rights employees at the Class II A Jakarta Women's Correctional Institution. This research is quantitative research. The sample used in this study amounted to 50 people. The sampling technique that will be used in this study is probability sampling using simple random sampling. Hypothesis testing carried out in this study is the Coefficient of Determination Test (R2), t-test and F-test using a significance level of 5% (0.05). The results of the test obtained (1) there is a positive and significant influence between organizational culture on employee work discipline, (2) there is a positive and significant influence between work motivation on employee work discipline, (3) and simultaneously there is a positive and significant influence between organizational culture and work motivation on employee work discipline